PERLINDUNGAN HUKUM PELAKU USAHA BISNIS RITEL TRADISIONAL TERHADAP PERKEMBANGAN RITEL MODERN DI KOTA PADANG - Mhd. Khadafi Abdullah (UNES Journal of Swara Justisia, 2018)
The writing of this scientific paper discusses the legal protection of TraditionalRetail Business Actors Against the Development of Modern Ritek in Padang City. Thebackground of this scientific work is the number of modern retail minimarkets as well asshopping centers that stand in line with the development of the city of Padang, withoutaccompanied by a clear regulation in accordance with what has been mandated by thelegislation in force. What causes traditional retailers to gain competition and theconversion of traditional retail customers to modern retailers. The aim of this scientificwork is to find out about the protection of legal protection for traditional retailers againstthe development of modern retail in the city of Padang. This scientific work usingdescriptive analysis methods that can be drawn conclusions are: Presidential RegulationNo. 112 of 2007 concerning the Arrangement and Guidance of Traditional Markets,Shopping Centers and Modern Shops and Regulation of the Minister of Trade No. 70 / MDAG / PER / 12/2013 concerning Structuring Guidelines Traditional Markets, ShoppingCenters and Modern Stores have provided legal protection to traditional retailers,mandating regional orders to refer to regional regulations on zoning in the establishmentof modern retail and traditional markets. But in fact the city government of Padang doesnot have regulations regarding the zoning.